How anonymity and norms influence costly support for environmental causes. (August 2018) - Vesely, Stepan; Klöckner, Christian A.
Abstract: Social norms are a key driver of pro-environmental action, but their influence may vary by context. An important contextual factor is behavior observability. We employ a laboratory quasi-experiment studying donations to environmental organizations under different levels of donor anonymity and under different levels of injunctive social norms. Decision observability amplifies the effect of norms: donations are 84% higher when observability is added to pro-environmental norms, compared to a setting with pro-environmental norms but anonymous decisions. Highlights: Decision observability promotes generosity towards environmental organizations. The main effect of injunctive social norms on donations is small. Decision observability augments the effect of injunctive social norms on donations. Norm-based interventions can benefit from taking contextual moderators into account.